2017
DOI: 10.1002/mrm.26687
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional quantification of vorticity and helicity from 3D cine PC‐MRI using finite‐element interpolations

Abstract: Purpose: We propose a 3D finite-element method for the quantification of vorticity and helicity density from 3D cine phase-contrast (PC) MRI. Methods: By using a 3D finite-element method, we seamlessly estimate velocity gradients in 3D. The robustness and convergence were analyzed using a combined Poiseuille and Lamb-Ossen equation. A computational fluid dynamics simulation was used to compared our method with others available in the literature. Additionally, we computed 3D maps for different 3D cine PC-MRI da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Traditionally, the transformation mapping has been the fundamental field sought in DIR applications, particularly in medical applications where the goal is to align the reference and target images [39]. However, recent applications of medical image quantification have highlighted the importance of guaranteeing certain accuracy and convergence when estimating stress tensor fields [38] and rotation tensor fields [37], due to their important connection to medical conditions. Further developments to improve the accuracy of the numerical solution, that are naturally developed within the finite-element framework adopted in this work, are the introduction of a-posteriori mesh refinement methods, where recent results in linear elasticity for mixed formulations with Neumann boundary conditions [16] can be extended to the case of DIR problems addressed here.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the transformation mapping has been the fundamental field sought in DIR applications, particularly in medical applications where the goal is to align the reference and target images [39]. However, recent applications of medical image quantification have highlighted the importance of guaranteeing certain accuracy and convergence when estimating stress tensor fields [38] and rotation tensor fields [37], due to their important connection to medical conditions. Further developments to improve the accuracy of the numerical solution, that are naturally developed within the finite-element framework adopted in this work, are the introduction of a-posteriori mesh refinement methods, where recent results in linear elasticity for mixed formulations with Neumann boundary conditions [16] can be extended to the case of DIR problems addressed here.…”
Section: Discussionmentioning
confidence: 99%
“…4D Flow allows a qualitative and quantitative analysis of several hemodynamic parameters. It has been applied extensively in the great vessels, particularly in the aorta [9][10][11] and in the left ventricle (LV) for assessing intraventricular flow in some cardiovascular diseases [12][13][14][15][16][17][18][19]. Previous studies have demonstrated that lower kinetic energy values in diastole are associated with the deterioration of ventricular filling, induced by morphological alteration commonly found in Fontan patients, mitral regurgitation, and LV dysfunction or remodeling [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we adapted a method for quantifying 4D Flow in the aorta [9][10][11]20]. We modified the methodology applied in the left ventricle to obtain several hemodynamic parameters from a single segmentation from a 4D Flow dataset and cine MRI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Pressure and pressure drop ( 3‐7 ): this is particularly relevant, since it is one of the main indicators of the severity of stenoses and eventual arterial blockages. The direct measure of a pressure (or even a pressure drop) could be performed by implanting a catheter, hence in a rather invasive way. The vorticity ( 8‐11 ): this quantity is monitored especially in the heart cavity and around cardiac valves. A too large vorticity could induce, for instance, haemolysis. The wall shear stress (WSS) ( 12‐14 ): this is related to the mechanical stress that the blood exerts on the endothelial cells, of paramount importance in aneurysms and plaque formation.…”
Section: Introductionmentioning
confidence: 99%